Fostering Tolerance and Cultural Preservation Through Community Empowerment: The Role of Islamic Values in Kampung Tahu Educational Tourism - Maghfiroh, Fachrial Lailatul; Arif Zunaidi; Moh. Asror Yusuf; Ahmad Syakur (Journal of Islamic Economics (JoIE), 2024)
Introduction: This paper explores the role of Islamic values in promoting tolerance and preserving cultural heritage through community empowerment in Kampung Tahu Educational Tourism. The study provides a background on how integrating Islamic principles with local wisdom contributes to sustainable development and strengthens social cohesion. Research Methods: Using a qualitative approach, data were collected through in-depth interviews, participant observation, and document analysis to examine the management strategies employed in empowering the Kampung Tahu community. Results: The findings reveal that the combination of religious values and cultural practices has positively impacted the community’s social and economic dynamics, enhancing unity and cultural preservation. The Kampung Tahu model demonstrates how educational tourism can drive economic growth while maintaining cultural identity. This research offers insights for other regions looking to implement similar strategies, emphasizing the significance of Islamic teachings in fostering harmony and sustainable development. Conclusion: The study concludes that religious and cultural integration is essential for community resilience and prosperity.